2013
DOI: 10.1515/ntrev-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Imaging modalities using magnetic nanoparticles – overview of the developments in recent years

Abstract: The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of " theranostics " combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Nanotechnology is of high potential for various medical applications, including cancer therapy [36], imaging [37], or tissue engineering [38]. However, just as any new technology, the use of nanoparticles in humans has concomitant risks.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology is of high potential for various medical applications, including cancer therapy [36], imaging [37], or tissue engineering [38]. However, just as any new technology, the use of nanoparticles in humans has concomitant risks.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Interestingly, when combined with stimuli-responsive polymers, additional features-such as thermo-responsiveness, valuable for sensing and drug delivery applications for instance-are conferred to the hybrid systems. Thanks to their unique properties, stimuli-RMPHs are employed in a wide range of research domains, including energy storage, 33 solid-phase extraction, 7 catalysis, 39,46 sensing/imaging, 5,47 biomedical devices 48 and cancer theranostics. 12,40,49 The following sections of this review illustrate the various strategies reported in the literature to develop stimuli-RMPHs of different structures and shapes.…”
Section: Stimuli-responsive Magnetic Polymer Hybridsmentioning
confidence: 99%
“…In vivo imaging technology may be used to dynamically observe the short-term distribution, homing and long-term survival of transplanted MSCs (4,5). The intravital tracer technique means that in stem cell transplantation, cells are able to be dynamically monitored in vivo to assess their migration and survival non-invasively (68). To obtain high definition images with high sensitivity, tracer technology for stem cells should be combined with multi-mode imaging (9).…”
Section: Introductionmentioning
confidence: 99%